CaNa[Cr(OH)6] – A Layered Hydroxochromate(III) with Ordered Brucite Structure and its Thermal Decomposition - Albrecht, Ralf; Hunger, Jens; Doert, Thomas; Ruck, Michael (Zeitschrift für Anorganische und Allgemeine Chemie, 2020)
Green single-crystals of the hydroxochromate(III) CaNa[Cr(OH)6] were grown under highly alkaline hydrothermal conditions at about 200 °C. The starting materials Ca(NO3)2·6H2O and Cr(NO3)3·9H2O were reacted in a mixture of water and sodium hydroxide with the molar ratio of 2.8:1. CaNa[Cr(OH)6] crystallizes in the non-centrosymmetric trigonal space group R3 with the lattice parameters a = 583.86(2) pm and c = 1428.73(6) pm [T = 100(1) K]. Characteristically, the crystals are reverse-obverse as well as inversion twins. The crystal structure is a stack of uncharged metal hydroxide layers, which can be regarded as a cation-ordered rhombohedral variant of the Mg(OH)2 (brucite) structure type. The oxidation state of chromium(III) and its coordination by hydroxide groups was confirmed by UV/Vis and IR spectroscopy, respectively. Temperature-dependent magnetic measurements revealed paramagnetic behavior with an effective moment of 3.82 μB per chromium atom. The thermal decomposition of CaNa[Cr(OH)6] takes place at about 225 °C, where the fast elimination of 1.5 equivalents of water is followed by the oxidation of chromium(III) to chromium(VI). Upon further heating to 1000 °C and 1200 °C, the intermediate decomposition products CaCrO4 and Na2CrO4 transform into the oxochromates(V) Ca5(CrO4)3O0.5 and Ca3(CrO4)2, respectively.
CRIS-Team Scopus Importer:2022-04-14
Keywords: Hydroxochromates; Chromium; Magnetic properties; Spectroscopy; Thermal analysis